174 SLE responder index (SRI) underestimates clinical response in musculoskeletal systemic lupus erythematosus. (April 2019) - Mahmoud, Khaled; Zayat, Ahmed; Md Yusof, Md Yuzaiful; Hensor, Elizabeth; Conaghan, Philip; Emery, Paul; Vital, Edward
Abstract : Background: Musuloskeletal (MSK) manifestations are common in SLE. Many recent clinical trials were negative or had small benefits vs. placebo. SRI is a common primary endpoint but has not been independently validated. Ultrasound is an objective measure of synovitis validated in inflammatory arthritis. We previously reported that in patients with inflammatory symptoms, 38% had swollen joints, 27% had subclinical inflammation (abnormal US but no clinically swollen joints) and 35% had no clinical or US inflammation. We also showed that subclinical tenosynovitis and PD were associated with significantly higher IgG, physician visual analogue score, tender joint count (Zayat et al. Rheumatology 2018). The purpose of the present study was to use ultrasound as a gold standard to evaluate clinical outcome measures of MSK lupus. Methods: A prospective pilot study was conducted in consecutive SLE patients with inflammatory musculoskeletal symptoms. Clinical assessments including SLEDAI-2K, BILAG-2004, 28-tender and swollen joint counts, physician and patient VAS and ultrasound were performed at 0, 2 and 4 weeks following 120 mg intramuscular methylprednisolone acetate. Responsiveness was analysed using changes and effect sizes using Cohens criteria. Results: 20 patients were recruited. 15/20 had clinical swelling at baseline. The others had abnormal ultrasound and/or early morning stiffness and tenderness. All clinical and US parameters were significantly improved at week 4 (all p0.01). Musculoskeletal-BILAG score improved in 16/20. Musculoskeletal-SLEDAI improved in 7/20. SRI-4 criteria were assessed in 19 patients with SLEDAI ≥4 at baseline met in 9/19 at 4 weeks. Effect sizes at 4 weeks were large (>0.5) for US (power Doppler and Greyscale), physician VAS and BILAG and medium (>0.3) for joint counts and SLEDAI. Large effect sizes for improvement in US greyscale and power Doppler were observed in both SRI responders (r=−0.51 and −0.56 respectively) and non-responders (r=−0.62 and −0.59) at 4 weeks. In SRI non-responders swollen joint counts improved by 20%, 50% and 70% in 7/10, 7/10 and 6/10 patients respectively. Conclusions: This is the first study to measure the responsiveness of clinical outcome measures in musculoskeletal SLE against an objective inflammation measure. BILAG-2004 and physician VAS were the most responsive clinical instruments. US was highly responsive in musculoskeletal SLE, while SLEDAI-2K and joint counts appeared suboptimal for detection of improvement. These results suggest that clinical trials based on the SLEDAI-2K and SRI-4 may underestimate the efficacy of therapy in SLE. Funding Source(s): LupusUK, NIHR